An Adaptive Blind Watermarking Algorithm for Color Image - Qiming Liu (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
This paper proposed a novel blind color digital watermarking algorithm based on Integer Discrete Wavelet Transform (IDWT) and Human Visual System (HVS). Firstly, color watermark image was processed into one dimension digital information, and color host image was converted into YIQ color space. Then, according to the features of HVS, encrypted watermark was embedded adaptively into the Y luminance component of the YIQ color space in IDWT domain. The proposed algorithm allowed extracting watermark without the help of original watermark and host image. Experiment results show that the embedded watermark is invisible and robust against common image attacks. DOI: http://dx.doi.org/10.11591/telkomnika.v11i1.1900